Tracking ammonia volatilization and fate from emission source to pristine ecosystem - Stratton, Joshua James, author; Borch, Thomas, advisor; Prieto, Amy, committee member; Bernstein, Elliot, committee member; Fisher, Ellen R., committee member; Collett, Jeffrey L., committee member (Colorado State University. Libraries, 2014)
Ammonia has been widely documented as a contributor to negative impacts on natural ecosystems. Agricultural related management has been closely tied to ammonia emission and therefore negative impacts of ammonia pollution. The aim of this research is to improve our current understanding of how ammonia is lost from native and agricultural soils and if nitrogen isotopes can be used to elucidate what sources of ammonia pollution affect native ecosystems the most. Rocky Mountain National Park (RMNP) has undergone ecosystem changes due to excessive nitrogen deposition in the forms of ammonium, nitrate and organic nitrogen. Due to uncertainty in source apportionment; the efficacy of nitrogen isotopes of ammonia to distinguish sources of ammonia deposited in RMNP was investigated. This study shows average δ¹⁵N isotopes of certain sources (beef cattle, dairy cattle production, wastewater treatment, cropland, urban) were distinguishable at this study's emission sites; however, the average δ¹⁵N isotope values measured at a RMNP site were not useful for identification of specific ammonia sources. Supplemental information (weekly integrations of gaseous and particulate reduced nitrogen, oxidized nitrogen, sulfur measurements, and HYSPLIT modeling) was needed to help pinpoint the likely sources of ammonia, such as agriculture and biomass burning, affecting RMNP. Moreover, this supplemental information was used to support the most likely reasons δ¹⁵N isotope values observed in gaseous ammonia and wet deposition were indistinguishable compared to emission sources. Little is known about the potential local contribution of ammonia from soils within RMNP. Thus, the goal of this study was also to develop a method for analysis of ammonia emissions from intact soil cores sampled from a sub-alpine grassland and forest within RMNP. Nitrogen wet deposition was monitored at the sampling location to investigate possible impacts on soil emissions of ammonia. Lastly, method development and analysis of formation of ammonia (urea hydrolysis), pH speciation (ammonia and ammonium), and vapor pressure (Henry constant) were investigated in beef and dairy feedlots to reveal important controls on ammonia emission. This research provides new information on the importance of post emission physical and chemical processes, such as source mixing, isotopic fractionation, and dry deposition, preventing the use of δ¹⁵N isotopes for source tracking without the use of complementary techniques, such as atmospheric modeling. Moreover this work provides further evidence indicating that natural emissions within RMNP are not major sources of reduced nitrogen in the RMNP airshed. Lastly, this work provides new chemical values for the Henry constant, acid dissociation constant, and urea hydrolysis rate constants in animal production systems and can be used to better estimate ammonia emissions from animal production to improve our current emission inventories.
Keywords: nitrogen; ammonia; isotope